PERANCANGAN DAN IMPLEMENTASI DATA LOSS PREVENTION SYSTEM DENGAN MENGGUNAKAN NETWORK ATTACHED STORAGE (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
There was no denying the data security issues deserved to be become a problem that must be solved. Data is one of thing which has become a reference for people to take a decision. Currently most of companies, colleges, and other institutions also rely on the data in their operations. It also the data is a very important part. In order that to preventing data losses, we are designed a system called Data Loss Prevention System which is a system that can be realize the client computer data backup scenarios are done on a scheduled basis. The backup data will be deposited on the infrastructure or Network Attached Storage (NAS) server computer so that a centralized data storage. In the processing of retrieving data from the server to the client computer, the system uses a protocol called Rsync.